HUBUNGAN GERAKAN BERULANG, POSTUR PERGELANGAN TANGAN, MASA KERJA DAN USIA TERHADAP KEJADIAN CARPAL TUNNEL SYNDROME PADA TUKANG BESI (Studi Kasus Pada Pekerja Pembentukan Tulangan Kolom, Proyek Pembangunan Apartemen Oleh PT X) - Hanna Vergia Mariana; Siswi Wijayanti; Ida Wahyuni (Jurnal Kesehatan Masyarakat (Undip), 2018)
Carpal Tunnel Syndrome (CTS) is the most common neurological disorder of the hands due to the suppression or "squeezing" of the peripheral nerves through this tunnel with typical symptoms of pain, numbness and tingling in the wrist, thumb, index finger, middle finger and half of ring finger. Any use of the wrist causing narrowing of the carpal tunnel or increasing pressure within this confined space may result in CTS. In the construction sector, iron workers are daily workers who are tasked working on various ironing activities such as making columns. These workers are at risk of having CTS in their hands as a result of their job. The purpose of this research is to analyze the association between repetitive movement, wrist posture, work period and age with CTS incident on iron workers at apartment development by PT X. The type of this research is observational analytic research with cross sectional study approach. This research uses RULA to measure wrist posture, Phalen’s Test and BCTQ Questionnaires to find out and describe incidence of CTS. The population and sample in this study were 36 workers. Based on statistical test using Chi-Square, there was an association between repetitive motion with CTS (p value = 0,018), there was an association between wrist posture and CTS (p value = 0,006), there was no association between work period with CTS (p value = 0,688) and also there was no association between age and CTS (p value = 0,729) on ironworker who made columns. Some recommendation for company are to be able to educate workers working with a good posture and stretch their wrist after working. For workers, always keep the wrist in a neutral position more often, loosen the hand grip and reduce energy used when twisting wire and also stretching after work.